Summer Squash Production in Miami-Dade County, Florida - D. Seal; S. Zhang; P. Dittmar; Yuncong Li; W. Klassen; Q. Wang; T. Olczyk (EDIS)
Summer squash is an important vegetable crop in Miami-Dade County. It is grown annually on about 6,000 acres and sold nationwide during the winter in the fresh market. This 16-page fact sheet describes the varieties of summer squash, land preparation and transplanting, what fertilizer to use, irrigation and freeze protection, disease management, insect management, weed management, harvest, and crop rotation.